O desenvolvimento do Programa Nacional de Alimentação Escolar no município de Francisco Beltrão - PR - Paz, Lidiane da (2016)
Family farming is predominant in Francisco Beltrão city, both the number of establishments, as in occupied area. The production is diversified, either in animal husbandry: poultry, pork, cattle and milk production, whether in crop production: vegetables, tubers, fruits, corn, wheat, soybeans. The type of production depends mainly on the economic classification of the family farm where the establishment is inserted. Thus constitute small shops with low insertion on the market and low production infrastructure, and others entered the market whose expertise and mechanization are bigger. The limits for the development of the research, was the family production for institutional market, the National School Meal Program - PNAE. The PNAE is the oldest social program in Brazil, had several changes throughout yours 60 years of implementation. Currently, the PNAE absorbs a significant portion of family production and is an important commercialization tool, especially for the less capitalized farmers. Although, the research reveals that in relation to the monetary value of trade, farmers producing processed foods, like pasteurized milk, cheese, eggs and certified meats, are the most benefited from the program. Another important aspect of PNAE is your emergency nature, aimed ensuring food to students in vulnerable situations. After the PNAE s decentralization (1994), it went on to be performed by states and municipalities. The research considers these two spheres to understand the development of the program in Francisco Beltrão. For this purpose, it was also considered the role of Cooperative Agriculture Integrated Family (COOPAFI), because it is through it that farmers, who produce no-processed food, trade to the PNAE, thus characterize their performance while articulating between family production and institutional market. During the research was realized that the relationships of family farming products commercialization, are characteristic of short circuits, which is the institutional trades, fairs, sale to domicile or establishment, in another words, have only one "middleman" between the producer and the final consumer.